DIGITAL MARKETING COMMUNICATION TO INCREASE CRSL STORE BRAND AWARENESS - Salim, Mufid; Rosdian, Erwin Dwi Sabna; Marta, Rustono Farady (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
CRSL Store is a clothing store or distribution company that produces various bags, backpacks, garments, jackets, headgear, and footwear. The CRSL brand attracted many people because of its unique products, which consisted of five adorable animal figures. CRSL indirectly undertakes a